2021
DOI: 10.3390/molecules26226816
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sample Preparation Strategies for Human Milk and Plasma Proteomics

Abstract: Sample preparation is the most critical step in proteomics as it directly affects the subset of proteins and peptides that can be reliably identified and quantified. Although a variety of efficient and reproducible sample preparation strategies have been developed, their applicability and efficacy depends much on the biological sample. Here, three approaches were evaluated for the human milk and plasma proteomes. Protein extracts were digested either in an ultrafiltration unit (filter-aided sample preparation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Enzymatic hydrolysis of protein samples was conducted using FASP according to a previous study ( 15 ), which seems to be the most effective approach for biological sample aliquots owing to the low miscleavage rate ( 16 ). To each protein sample (100 μg) 8 M urea was added to obtain a final volume of 200 μL, and then DL-dithiothreitol was added until a final concentration of 10 mM; this mixture was incubated at 56°C for 30 min to destroy the intramolecular and intermolecular disulfide bonds.…”
Section: Methodsmentioning
confidence: 99%
“…Enzymatic hydrolysis of protein samples was conducted using FASP according to a previous study ( 15 ), which seems to be the most effective approach for biological sample aliquots owing to the low miscleavage rate ( 16 ). To each protein sample (100 μg) 8 M urea was added to obtain a final volume of 200 μL, and then DL-dithiothreitol was added until a final concentration of 10 mM; this mixture was incubated at 56°C for 30 min to destroy the intramolecular and intermolecular disulfide bonds.…”
Section: Methodsmentioning
confidence: 99%
“…For protein depletion, it has been reported that MARS-14 columns do not efficiently capture targeted proteins. 27 Therefore, a 90% MARS-14 DE was chosen as the desired specification because it is dependent on protein concentrations obtained from the BCA assay and not target identification that would require an LC−MS/MS check. If the results were OOS, participant plasma depletions were paused, and another QC std aliquot was depleted for confirmation.…”
Section: Mars-14 Depletion Efficiencymentioning
confidence: 99%
“…Ideally, sample preparation workflows should be designed to minimize sample handling and operator-generated biases. However, sample preparation can be tedious, error-prone, and susceptible to reproducibility issues. Automation with robotic liquid handlers relieves the burden of sample preparation while also reducing variability between operators and samples . These handlers are also embraced for reducing the cost of routine biomarker discovery and development .…”
Section: Introductionmentioning
confidence: 99%
“…In this manner, SP3 is recognized as a more versatile and efficient approach to sample preparation, enhancing the adaptability of protocols and facilitating the use of reagents previously considered off-limits for MS-based proteomics. Despite previous studies successfully comparing widely used MS sample preparation methods (e.g., classical ISD and FASP) [12][13][14], there has been a notable gap in research, and a systematic evaluation of different lysis buffer reagents using a single sample preparation strategy has been missing. Furthermore, lysates can be utilized to enrich for interaction partners before the analysis by MS.…”
Section: Introductionmentioning
confidence: 99%